Cryoballoon Ablation of Atrial Fibrillation Without Demonstration of Pulmonary Vein Occlusion—The Simplify Cryo Study - Kühne, Michael; Knecht, Sven; Spies, Florian; Aeschbacher, Stefanie; Haaf, Philip; Zellweger, Michael; Schaer, Beat; Osswald, Stefan; Sticherling, Christian (Frontiers in Cardiovascular Medicine, 2021)
Background: The demonstration of pulmonary vein (PV) occlusion is routinely performed and considered a prerequisite for successful cryoballoon (CB) ablation of atrial fibrillation (AF). The purpose of this study was to assess the feasibility and impact on procedural parameters and outcome of a standardized procedural protocol without demonstrating PV occlusion. Methods and Results: Consecutive patients undergoing CB pulmonary vein isolation (PVI) were studied. After cMRI assessment, patients treated by PVI using a novel no-contrast (NC) protocol without routine contrast injections to demonstrate PV occlusion (NC group) were compared to patients undergoing PVI with contrast injections to demonstrate PV occlusion (standard group). One hundred patients with paroxysmal or persistent AF (age 61 ± 10 years, ejection fraction 59 ± 11%, left atrial volume index 37.2 ± 2.0 mL/m2) were studied. The NC protocol was feasible in 72 of 75 patients (96%). Total procedure time and fluoroscopy time were 64.0 ± 14.1 min and 11.0 ± 4.6 min in the NC group and 92.0 ± 25.3 min and 18.0 ± 6.0 min in the standard group, respectively (all p < 0.001). Dose area product was 368 ± 362 cGy*cm2 in the NC group compared to 1928 ± 1541 cGy*cm2 in the standard group (p < 0.001). Forty-five of 75 patients (60%) in the NC group and 16 of 25 patients (64%) in the standard group remained in stable sinus rhythm after a single PVI and a 1-year follow-up (p = 0.815). Conclusions: Performing CB ablation without using contrast injections to demonstrate PV occlusion was feasible, resulted in reduced radiation exposure, and increased the efficiency of the procedure.